2006
DOI: 10.1051/0004-6361:20066548
|View full text |Cite
|
Sign up to set email alerts
|

The variable X-ray spectrum of Markarian 766

Abstract: Aims. We analyse a long XMM-Newton observation of the narrow-line Seyfert 1 galaxy Mrk 766, using the marked spectral variability on timescales >20 ks to separate components in the X-ray spectrum.Methods. Principal components analysis is used to identify distinct emission components in the X-ray spectrum, possible alternative physical models for those components are then compared statistically. Results. The source spectral variability is well-explained by additive variations, with smaller extra contributions m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
160
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(170 citation statements)
references
References 52 publications
10
160
0
Order By: Relevance
“…In fact, several authors have demonstrated that accretion disk winds/outflows might well imprint also other spectral signatures in the X-ray spectra of AGNs besides blue-shifted Fe K absorption lines (e.g., Pounds & Reeves 2009, and references therein). For instance, Sim et al (2008) and Sim et al (2010) have been able to successfully reproduce the 2−10 keV spectra of two bright sources of our sample in which the detection of strong blue-shifted Fe K absorption lines in their XMM-Newton spectra were already reported, namely Mrk 766 (from Miller et al 2007) and PG 1211+143 (from Pounds et al 2003a), using their AGN accretion disk wind model. Notably, the authors have been able to account for both emission and absorption features in a physically self-consistent way.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In fact, several authors have demonstrated that accretion disk winds/outflows might well imprint also other spectral signatures in the X-ray spectra of AGNs besides blue-shifted Fe K absorption lines (e.g., Pounds & Reeves 2009, and references therein). For instance, Sim et al (2008) and Sim et al (2010) have been able to successfully reproduce the 2−10 keV spectra of two bright sources of our sample in which the detection of strong blue-shifted Fe K absorption lines in their XMM-Newton spectra were already reported, namely Mrk 766 (from Miller et al 2007) and PG 1211+143 (from Pounds et al 2003a), using their AGN accretion disk wind model. Notably, the authors have been able to account for both emission and absorption features in a physically self-consistent way.…”
Section: Discussionmentioning
confidence: 53%
“…We interpreted such features as blue-shifted Fe XXVI Lyα absorption lines. The presence of the first one at a rest-frame energy of ∼7.3 keV has already been suggested by Miller et al (2007) and Turner et al (2007).…”
Section: Appendix B: Notes On Single Sourcesmentioning
confidence: 54%
“…This strongly suggests that the absorption material could be observed in the spectrum through Fe Kshell absorption lines from Fe xxv and Fe xxvi (e.g., Sim et al 2008;Schurch et al 2009;Sim et al 2010), in complete agreement with our detection of UFOs. In particular, Sim et al (2008) and Sim et al (2010) used their accretion disk wind model to successfully reproduce the 2-10 keV spectra of two bright radioquiet AGNs in which strong blueshifted Fe K absorption lines were detected in their XMM-Newton spectra, namely, Mrk 766 (from Miller et al 2007) and PG 1211+143 (from Pounds et al 2003). Notably, the authors have been able to account for both emission and absorption features in a physically self-consistent way and demonstrated that accretion disk winds/outflows might well imprint also other spectral signatures in the X-ray spectra of AGNs (e.g., Pounds & Reeves 2009 and references therein).…”
Section: Physical Properties Of Ultra-fast Outflowsmentioning
confidence: 99%
“…Among the possible physical interpretations of these features are an origin in the accretion disc (e.g. Reeves et al 2001;Pounds et al 2001;Miller et al 2007) or produced in photoionised circumnuclear matter (e.g. Bianchi & Matt 2002;Bianchi et al 2005); • Fe I 6.4 keV Compton shoulder (G i ).…”
Section: Spectral Modelmentioning
confidence: 99%